Extracellular Signal-Regulated Kinase Induces the Megakaryocyte GPIIb/CD41 Gene through MafB/Kreisler - Sevinsky, Joel R. (American Society for Microbiology, 2004)
Extracellular signal-regulated kinase (ERK) facilitates cell cycle progression in most mammalian cells, but in certain cell types prolonged signaling through this pathway promotes differentiation and lineage-specific gene expression through mechanisms that are poorly understood. Here, we characterize the transcriptional regulation of platelet GPIIb integrin (CD41) by ERK during megakaryocyte differentiation. ERK-dependent transactivation involves the proximal promoter of GPIIb within 114 bp upstream of the transcriptional start site. GATA, Ets, and Sp1 consensus sequences within this region are each necessary and function combinatorially in ERK-activated transcription. MafB/Kreisler is induced in response to ERK and synergizes with GATA and Ets to enhance transcription from the proximal promoter. The requirement for MafB in promoter regulation is demonstrated by inhibition of transactivation following dominant-negative or antisense suppression of MafB function. Thus, ERK promotes megakaryocyte differentiation by coordinate regulation of nuclear factors that synergize in GPIIb promoter regulation. These results establish a novel role for MafB as a regulator of ERK-induced gene expression.